THE EFFECTIVENESS OF COOPERATIVE LANGUAGE LEARNING IN TEACHING VOCABULARY - Wahyu Trimastuti (IJET (Indonesian Journal of English Teaching), 2016)
This study aims to determine whether the Cooperative Language Teaching and Learning method is more effective than the traditional learning to teach vocabulary. This is an experimental quantitative research. The population for this study is freshmen majoring in management. The use of Cooperative Language Teaching and Learning method through engineering teams-games-tournament (TGT) in the English vocabulary learning is considered to be effective, creative, and fun to increase the students’ motivation to learn and to improve their vocabulary mastery. The findings showed that the Cooperative Language Teaching and Learning is an effective method to teach vocabulary. It is, thus, recommended that (1) the Cooperative Language Learning and Teaching improve the students’ ability to remember vocabulary, (2) students are expected to be more active in the learning process in order to improve the ability to solve the problem of vocabulary (3) the results of this study can be used as an initial step to hold further research.